Conceptualizing Adaptive Curriculum: A Holistic Approach to Inclusive Learning: Konseptualisasi Kurikulum Adaptif: Pendekatan Holistik dalam Pembelajaran Inklusif - Ilham Syachbana, Aqsyal; Rahmah, Aulia (CV. Media Publikasi Profesional, 2023)
Adaptive curriculum is an effort to provide quality learning that suits the needs of students, including students with special needs. Adaptive curriculum with a holistic approach can be a solution to realize an inclusive education system. Inclusive education aims to accommodate the diversity and individual differences of students, so that they can learn together without discrimination. Inclusive education that implements adaptive curriculum with a holistic approach can ensure equal access and participation for all students. Adaptive curriculum that is responsive to the individual needs of students can support the creation of an inclusive learning environment, where all students can actively and effectively engage in the learning process. The holistic approach in adaptive curriculum allows for adjustments to materials, methods, and learning evaluations according to the characteristics and needs of each student. Thus, inclusive education that implements adaptive curriculum with a holistic approach can ensure equal access and participation for all students, including those who require special support.